Making Sense of Test-Based Accountability in Education - Hamilton, Laura S. (RAND Corporation, 2002)
Test-based accountability systems that attach high stakes to standardized test results have raised a number of issues on educational assessment and accountability. Do these high-stakes tests measure student achievement accurately? How can policymakers and educators attach the right consequences to the results of these tests? And what kinds of tradeoffs do these testing policies introduce? This book responds to the growing emphasis on high-stakes testing and offers recommendations for more-effective test-based accountability systems.